(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article provides information about the teaching methods and principles of organizing physical education, sports health activities, the purpose and content, the formation of materials, and the types of discipline.